Correlation Between the Number of Removed Lymph Nodes and Ratio of Lymph Node Metastasis in Stage IB-IIA Cervical Cancer - Turan, Taner; Keskin, Levent; İlhan, Tüyan; Tulunay, Gökhan; Boran, Nurettin; Özer, Süha; Demir, Faruk; Köse, Faruk (Gynecology Obstetrics & Reproductive Medicine, 2010)
OBJECTIVE: Understanding the relation between the numbers of removed lymph node and getting positive lymph node. STUDY DESIGN: Medical records of 250 patients diagnosed as stage IB-IIA cervical cancer and treated with type III radical hysterectomy plus systematic pelvic and para-aortic lymphadenectomy in between January 1993 and December 2007 were evaluated. Clinical stage IB1 tumor was present in 171 patients, IB2 in 30 patients and IIA in 49 patients. RESULTS: The mean age of patients was 53.9 years. The metastatic node was determined in 34% of patients. The median number of removed nodes was 52 (13-160). It was removed 20 or less lymph nodes in 3.6% of patients, 21-30 lymph nodes removed in 11.6% of patients, 31-40 lymph nodes in 18.4% of patients, 41-50 lymph nodes in 14.4% of patients, 51- 60 lymph nodes in 15.6% of patients, 61-70 lymph nodes in 15.6% of patients, 71- 80 lymph nodes in 10% of patients and more than 80 in 10.8% of patients. The positive lymph node incidence was at minimum (11.1 %) in the ≤20 lymph nodes removed group and incidence was at maximum (60.4%) was observed in 31-40 lymph nodes removed group. However, there was no significant relationship between the number of removed nodes and getting positive lymph nodes. CONCLUSION: There was no relationship between number of lymph nodes removed and the chance of finding metastasis. However, the percentage of positive lymph nodes was lowest in the group where lowest number of nodes was removed.